2016
DOI: 10.1111/and.12562
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endopeptidase inhibition on the relaxation response of isolated human penile erectile tissue to vasoactive peptides

Abstract: Peptides, such as CNP, CGRP and VIP, are involved in the function of male penile erectile tissue. Tissue levels of said peptides are controlled by the endopeptidase enzymes. Theoretically, the inhibition of the degradation of CNP, CGRP and/or VIP should result in an enhancement in penile smooth muscle relaxation. The effects were investigated of CNP or VIP (0.1 nm-1 μm), without and following pre-exposure of the tissue to a threshold concentration of the endopeptidase inhibitor KC 12615 (10 μm, for 20 min), on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, a recent in vitro study conducted on human small arteries revealed no effects of NEP inhibition on the vasodilator action of CNP (Dalzell et al., ). In human CC, the combination of CNP or VIP plus KC 12615 failed to produce a significant enhancement in the relaxation of the tissue brought about by transmural electrical field stimulation (Rahardjo et al., ). In a clinical setting, NEP inhibition did not exert any potentiation of acute cardiovascular actions of a subsequent administration of CNP (Brandt, Mattingly, Clavell, Barclay, & Burnett, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent in vitro study conducted on human small arteries revealed no effects of NEP inhibition on the vasodilator action of CNP (Dalzell et al., ). In human CC, the combination of CNP or VIP plus KC 12615 failed to produce a significant enhancement in the relaxation of the tissue brought about by transmural electrical field stimulation (Rahardjo et al., ). In a clinical setting, NEP inhibition did not exert any potentiation of acute cardiovascular actions of a subsequent administration of CNP (Brandt, Mattingly, Clavell, Barclay, & Burnett, ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, the potential use of endopeptidase inhibitors has been assumed to treat certain types of female sexual dysfunction (FSD) (Rahardjo et al., ). In a recent study using human CC, an enhancement was registered in the accumulation of cyclic GMP in the presence of CNP plus KC 12615 (Rahardjo et al., ). Up until today, no study has evaluated the effects of endopeptidase inhibitors on the contraction response of human CC.…”
Section: Introductionmentioning
confidence: 95%